2007
DOI: 10.3174/ajnr.a0641
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antiplatelet Therapy on Thromboembolic Complications of Elective Coil Embolization of Cerebral Aneurysms

Abstract: BACKGROUND AND PURPOSE:Thromboembolic events are the most common complications of elective coil embolization of cerebral aneurysms. Administration of oral clopidogrel and/or aspirin could lower the thromboembolic complication rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
91
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 11 publications
6
91
0
1
Order By: Relevance
“…1,15 Prior studies in coil embolization procedures have demonstrated that symptomatic thromboembolic complications (transient ischemic attack or stroke within 60 days) occurred in 4 (16%) of 25 cases when no antiplatelet drugs were given, in 2 (2.3%) of 86 cases when antiplatelet drugs were administered only after embolization, and in 5 (1.9%) of 258 cases when antiplatelet drugs were administered before and after embolization. 19 Our current practices reflect these observations. We tend to pretreat all of our patients with oral aspirin, 81 or 325 mg daily, unless contraindicated by an aspirin allergy.…”
Section: Frequency Of Complicationssupporting
confidence: 58%
See 2 more Smart Citations
“…1,15 Prior studies in coil embolization procedures have demonstrated that symptomatic thromboembolic complications (transient ischemic attack or stroke within 60 days) occurred in 4 (16%) of 25 cases when no antiplatelet drugs were given, in 2 (2.3%) of 86 cases when antiplatelet drugs were administered only after embolization, and in 5 (1.9%) of 258 cases when antiplatelet drugs were administered before and after embolization. 19 Our current practices reflect these observations. We tend to pretreat all of our patients with oral aspirin, 81 or 325 mg daily, unless contraindicated by an aspirin allergy.…”
Section: Frequency Of Complicationssupporting
confidence: 58%
“…Heparin is generally discontinued at the conclusion of the procedure. 19 Previous studies have not revealed significant differences in the complication rate between balloon-assisted coiling and simple coil embolization. 12 In our series, 4 of 6 ischemic strokes occurred in patients treated with simple coil embolization, and 2 of 6 ischemic strokes occurred in patients treated with stent-assisted coiling.…”
Section: Frequency Of Complicationsmentioning
confidence: 95%
See 1 more Smart Citation
“…11,21,22 However, patients in these studies regarding antiplatelet resistance were mostly those with atherosclerotic steno-occlusive disease, especially in cardiointerventions. 23,24 Unlike atherosclerotic vessels, unruptured aneurysms do not always cause significant atherosclerotic burden.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies support the idea that clopidogrel resistance can increase postprocedural thromboembolic complications, and our preliminary study showed similar results. 4,11,12,22 Hwang et al 10 recently reported that abnormal PRUs were associated with symptomatic infarction and that modified antiplatelet preparation could reduce the rate of thromboembolic events in coil embolization. In contrast, in this study, the occurrence of immediate postprocedural thromboembolic infarction was not closely associated with antiplatelet hyporesponders.…”
Section: Discussionmentioning
confidence: 99%